2007
DOI: 10.1159/000099985
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Collagen Gel Droplet Embedded Drug Sensitivity Test to Determine Drug Sensitivity against Ovarian Mature Cystic Teratoma with Malignant Transformation to Adenocarcinoma: A Case Report

Abstract: Background: The collagen gel droplet embedded drug sensitivity test (CD-DST) is a new anticancer drug sensitivity test that only requires a small number of cells. We report the use of this test in the choice of adjuvant chemotherapy for treatment of a rare case of ovarian cancer involving malignant transformation of ovarian mature cystic teratoma. Case Report: The patient was a 70-year-old female with an ovarian tumor, pleural effusion, carcinomatous ascites and a chest wall tumor. The histopathological diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The collagen gel droplet embedded culutre-drug sensitivity test (CD-DST) is an anticancer drug sensitivity test that requires only a small number of cells (3x10 3 per droplet) (2-4). The clinical usefulness of CD-DST for colon (5), breast (6) and gastric (7) cancers and even certain rare cases of solid tumors, such as ovarian mature cystic teratoma with malignant transformation to adenocarcinoma (8), have been reported. Yabushita et al (9) found a strong correlation between clinical outcome and CD-DST results for anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The collagen gel droplet embedded culutre-drug sensitivity test (CD-DST) is an anticancer drug sensitivity test that requires only a small number of cells (3x10 3 per droplet) (2-4). The clinical usefulness of CD-DST for colon (5), breast (6) and gastric (7) cancers and even certain rare cases of solid tumors, such as ovarian mature cystic teratoma with malignant transformation to adenocarcinoma (8), have been reported. Yabushita et al (9) found a strong correlation between clinical outcome and CD-DST results for anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%